Tech Development Through HRM Driving Innovation with Knowledge-Based Cultures. - Gürlek, Mert (Emerald points., 2020)
This book argues that knowledge management and HRM systems should be integrated. This integration provides the foundation for designing knowledge-oriented high-performance HR practices.